Handheld surface‐enhanced Raman scattering identification of dye chemical composition in felt‐tip pen drawings. (21st June 2018) - Saviello, Daniela; Di Gioia, Alexandra; Turenne, Pierre‐Ives; Trabace, Maddalena; Giorgi, Rodorico; Mirabile, Antonio; Baglioni, Piero; Iacopino, Daniela
Abstract: A handheld Raman spectrometer is used for the first time to perform surface‐enhanced Raman scattering (SERS) analysis of felt‐tip pen drawings on paper. The use of SERS combined with near‐infrared excitation wavelength allows overcoming the strong fluorescence background interference so that diagnostic spectra are obtained from drawings made by 18 pens of 10 different colors and five different brands. The analysis reveals that often mixtures of two or more dyes are used by pen manufactures in order to obtain the desired color hue and also that same colors from different pen brands often display different dye composition. Handheld SERS is also used for revealing the dye content of historical felt tip pens extensively used by the Italian film director Federico Fellini. The results from this work open the way to the use of handheld instrumentation for analysis of ink‐based art works and documents and also provide a starting point towards the creation of a reference SERS database for dye identification. Abstract : Handheld surface‐enhanced Raman scattering (SERS) is used for the first time to analyze the chemical content of commercial felt‐tip pens. A total of 18 drawings from pens of different color and brands are analyzed. In the majority of the cases, SERS provides enhanced spectral response compared with normal Raman and allows the identification of dye chemical composition of the analyzed ink mixtures. The chemical makeup of historical felt‐tip pens used by Federico Fellini is also revealed by the analysis.